Fatigue equivalent load approach for fatigue design - Raoult Ida; Delattre Benoit (MATEC Web of Conferences, 2019)
Industrial structures undergo complex loading often unsuitable for the design and validation phases of their development. Engineers seek simplified signals to replace them, yet equivalent in terms of fatigue. A general framework for the construction of fatigue equivalent loads is presented, intended to take into account some uncertainty on the structure to which it will apply. The guiding idea is to describe this uncertainty thanks to parameters of a model of the structure, and then to assure the equivalence of damage or failure behavior over the whole range of expected parameters. The approach is applied in the case of structures undergoing multiple inputs of concentrated force.